2013
DOI: 10.1016/j.jpba.2013.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sildenafil citrate tablets of different sources by near infrared chemical imaging and chemometric tools

Abstract: In this paper the chemical imaging technique by near infrared spectroscopy was applied for characterization of drug formulations in tablets of sildenafil citrate of different sources. This work is original and has never been published because it was used the sildenafil citrate, including in the commercial one called "Viagra".In the first stage of the study, a chemometric method based on multivariate curve resolution was properly chosen for the development of the distribution map of concentrations of the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The pharmaceutical industry brings the Raman imaging into focus due to its advantages in local determination of chemical and physical characteristics along the original and generic research and development. Numerous papers have reported that this technique is well suitable for analysing polymorphic forms [7], exploring relationship of the ingredients or determining the composition of counterfeits [8,9]. There is a need for extending this method to investigate the distributional homogeneity of blends.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmaceutical industry brings the Raman imaging into focus due to its advantages in local determination of chemical and physical characteristics along the original and generic research and development. Numerous papers have reported that this technique is well suitable for analysing polymorphic forms [7], exploring relationship of the ingredients or determining the composition of counterfeits [8,9]. There is a need for extending this method to investigate the distributional homogeneity of blends.…”
Section: Introductionmentioning
confidence: 99%
“…Besides qualitative and quantitative characterization of ingredients in bulk materials, it can provide further information about spatial distribution of major and even minor (sometimes trace) components [1]. Many diverse issues have been already solved using chemical imaging in the field of life sciences and diagnostics [2,3], forensic sciences and counterfeiting [4,5], food analysis [6,7], plastics [8] and artworks [9]. In recent years, the application of this approach has sparked explosively growing interest particularly in the pharmaceutical industry [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques were assisted by the use of chemometric methods for the treatment of a high number of data (spectra and variables). NIR and Raman spectroscopies are well described in the literature and their use is growing in the pharmaceutical and forensic fields, but no report has been found for the specific study of anabolic products. They are based on the interaction of the light with the sample for the study of molecular vibrations in a material.…”
Section: Introductionmentioning
confidence: 99%